Neurotropism and blood-brain barrier involvement in COVID-19 - Takashi Fujimoto; Takashi Fujimoto; Michelle A. Erickson; Michelle A. Erickson; William A. Banks; William A. Banks (Frontiers Media S.A., 2022)
The global pandemic of coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) persists despite the progress of vaccination and increased natural immunity. SARS-CoV-2 is associated not only with pneumonia and acute respiratory distress, but also with many symptoms related to the central nervous system (CNS), including loss of the sense of taste and smell, headache, convulsions, visual disturbances, and impaired consciousness. In addition, the virus has been implicated in CNS diseases such as cerebral hemorrhage, cerebral infarction, and encephalitis. SARS-CoV-2 binds to the receptor angiotensin-converting enzyme 2 (ACE2), which is used by the virus as a cell entry receptor. Although the mechanism by which SARS-CoV-2 enters the brain is still unclear, the possibility of direct entry through the olfactory nerve tract and entry into the brain through the blood-brain barrier (BBB) and blood-cerebrospinal fluid barrier (BCSFB) via blood circulation is indicated. The BBB likely serves as a site of entry for SARS-CoV-2 into the brain, and possibly contributes to the CNS symptoms of COVID-19 due to its dysfunction as a result of SARS-CoV-2 infection. The present review will focus on the effects of COVID-19 on the CNS, particularly on the BBB related cells involved.